The Real Impact of Target Therapy in Breast Cancer Patients: Between Hope and Reality - Bordonaro, Sebastiano; Berretta, Massimiliano; Tralongo, Antonino C.; Clementi, Silvia; Stanzione, Brigida; Tralongo, Paolo (Current Cancer Drug Targets, 2018)
Over the last 15 years, we have seen a huge expansion of the development of drugs directed against biomolecular targets within breast cancer cells. The over-expression of certain receptors (ER, PgR, HER-2, VEGF-R), as well as alteration of several intracellular signal transduction pathways (the PI3K-AKT-mTOR pathway, MEK-MAPK pathway, loss of PTEN, etc ...) has a great impact on the likelihood of recurrence and progression of the disease, influencing the natural history of breast cancer. The recent biomolecular classification of breast cancer (Luminal A / B, HER2- driven, Basal Like) allowed finally to identify specific treatments against molecular target to associate or not to traditional chemotherapy, and to use in relation to the prognosis of the disease. In the following paragraphs, we will set out the major targeted drug that have received indications in breast cancer, both in the localized and in advanced disease, referring to the specific target (hormonal receptors, HER2, VEGF, m-TOR, PARP etc ...).
Keywords: receptors